Unveiling neonatal intestinal obstruction due to total colonic atresia: A case report - Arbi, Fawad Mueen; Anjum, Muhammad Zulfiqar; Iqbal, Zeeshan; Fatima, Seerat (Journal of Neonatal Surgery, 2024)
Background: Total colonic atresia is an uncommon congenital anomaly associated with neonatal intestinal obstruction, often necessitating prompt diagnosis and surgical intervention to prevent life-threatening complications. Understanding the etiology and optimal management strategies is crucial for ensuring favorable outcomes. Case Presentation: We present a case of a full-term male neonate with total colonic atresia, who presented with failure to pass meconium, abdominal distension, and vomiting. Diagnostic imaging confirmed intestinal obstruction, leading to surgical exploration revealing an atretic colon extending from the Ileocolic Junction to the Rectosigmoid Junction. An ileostomy was performed, followed by meticulous postoperative care, resulting in a successful resolution of symptoms and discharge from the hospital. Conclusion: Timely recognition and staged surgical management are paramount in addressing total colonic atresia, emphasizing the importance of early intervention for optimal patient outcomes. Long-term follow-up and comprehensive care are essential to ensure the overall well-being of affected newborns.